2000
DOI: 10.1016/s0002-9440(10)64709-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase in Cyclin-D1 Expression and Accelerated Entry of Mouse Hepatocytes into S Phase after Administration of the Mitogen 1,4-Bis[2-(3,5-Dichloropyridyloxy)] Benzene

Abstract: We have previously demonstrated that hepatocyte proliferation induced by the mitogen 1,4-bis[2-(3,5-dichloropyridyloxy)] benzene (TCPOBOP) is independent of changes in cytokines, immediate early genes, and transcription factors that are considered to be necessary for regeneration of the liver after partial hepatectomy (PH) or necrosis. To further investigate the differences between mitogen-induced mouse hepatocyte proliferation and liver regeneration after PH, we have measured the expression of cyclin D1, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 50 publications
7
71
0
Order By: Relevance
“…As to the liver, enhanced expression of cyclin D1 before the onset of DNA synthesis has been reported in liver regeneration after two-thirds partial hepatectomy 7,24,34,35 and represents one of the earliest events following treatment with chemicals that have mitogenic activity for rodent liver, especially ligands of nuclear receptors of the steroid/thyroid receptor superfamily 7,24 ; however, the exact role and relevance of cyclin D1 in hepatocyte proliferation in vivo is not clear. The present results clearly show that, although lack of cyclin D1 might delay the entry into S phase for a relatively short time, this cyclin is not essential for liver growth and hepatocyte proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…As to the liver, enhanced expression of cyclin D1 before the onset of DNA synthesis has been reported in liver regeneration after two-thirds partial hepatectomy 7,24,34,35 and represents one of the earliest events following treatment with chemicals that have mitogenic activity for rodent liver, especially ligands of nuclear receptors of the steroid/thyroid receptor superfamily 7,24 ; however, the exact role and relevance of cyclin D1 in hepatocyte proliferation in vivo is not clear. The present results clearly show that, although lack of cyclin D1 might delay the entry into S phase for a relatively short time, this cyclin is not essential for liver growth and hepatocyte proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that cyclin D1 is markedly up-regulated by the chemical mitogen TCPOBOP as well as triiodothyronine in vivo, whereas cyclin D3 shows little change in expression. 57,58 This suggests that mitogenic nuclear receptors may induce hepatocyte proliferation via direct induction of cyclin D1, but have little effect on cyclin D3. These data further argue that cyclins D1 and D3 play a fundamentally distinct role in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the hepatocyte response to T3 is associated with a rapid induction of cyclin D1 and an accelerated entry into the S phase (Pibiri et al 2001). Based on the finding that an early induction of cyclin D1 was found following treatment with other ligands with mitogenic activity (Ledda-Columbano et al 2000a), it has been proposed that cyclin D1 is a direct target gene of the transcriptional activity of these receptors (Ledda-Columbano & Columbano 2003).…”
Section: Introductionmentioning
confidence: 99%